Use of Rapid Drug Desensitization in Delayed Hypersensitivity Reactions to Chemotherapy and Monoclonal Antibodies - Vega, Arantza; Peña, M. Isabel; Torrado, Inés (Frontiers in Allergy, 2022)
Background: Rapid drug desensitization (RDD) allows first-line therapies in patients with immediate drug hypersensitivity reactions (DHR) to chemotherapeutic drugs (ChD) and monoclonal antibodies (mAb). Desensitization in delayed drug reactions has traditionally used slow protocols of several days-weeks; RDD protocols have been scarcely reported. Patients and method: We retrospective analyzed the patients referred to the Allergy Department who had experienced a delayed DHR (> 6 hours) related to a ChD or mAb and underwent a RDD protocol. The rate of successful administration of the offending drug and the presence of adverse reactions were evaluated. Results: A total of 93 RDD were performed in 11 patients (6 men, 5 women, with a median age of 61 years). The primary DHR were maculo-papular exanthema (MPE) (8); generalized delayed urticaria (1); MPE with pustulosis and facial edema (1); and facial edema with desquamative eczema (1). Mean time for the onset of symptoms was 3 days (range 1-16 days). RDD was performed using an 8-13 step protocol with temozolomide (25), bendamustine (4), rituximab (9), infliximab (24), gemcitabine (23) and docetaxel (8) within 4.6 - 6.5 hours. Sixteen breakthrough reactions were reported during the RDD (17.2 %) in 5 patients, all mild reactions: 11 delayed, 5 immediate. All patients completed their treatment. Conclusions: RDD is a potential safe and effective procedure in patients suffering from delayed reactions to ChD and mAb. It allows them to receive full treatment in a short period of time, reducing time and hospital visits.